Adaptive Help Seeking Related to Academic Resilience of Final Year College Student with Special Needs - Prakosha, Donni; Sunardi, Sunardi; Sugini, Sugini; Anwar, Mohammad; Martika, Tias; Martha, Vania; Afiliana, Ersya (Teaching, Learning, and Development, 2026)
This paper aims to describe and understand the essence of the lived experiences of final-year college students with special needs regarding their adaptive help-seeking and academic resilience. The research approach used is a qualitative study involving students with various types of disabilities. Purposive sampling of 9 student were selected for the semi-structured interviews. Cassidy’s Academic Resilience Scale (ARS) was used as the interview guided. Data triangulation was used throughout the research to ensure integrated analysis. The result shows that participants described their parents as sources of emotional reassurance and moral encouragement. Besides, the theme of Peer Support reveals that the respondent has a mature strategy for maintaining their mental well-being. This study demonstrates that both parental and peer support are essential resources in sustaining the academic resilience of final year students with disabilities. While parental support was identified as the primary motivator, providing a strong foundation of care, encouragement, and responsibility, peer support emerged as equally vital in maintaining on going motivation and well-being.